84.8k views
5 votes
Simply the expression below. Explain which rules of exponents you used to simplify the expression.

Simply the expression below. Explain which rules of exponents you used to simplify-example-1
User Hungneox
by
5.5k points

1 Answer

5 votes

The expression is given to be:


(xy^7)^3/ y^(14)

STEP 1: Applying the exponent rule of brackets:


(x^m)^n=x^(m* n)

Therefore, the expression becomes:


\begin{gathered} \Rightarrow x^3\cdot y^(7*3)/ y^(14) \\ \Rightarrow x^3\cdot y^(21)/ y^(14) \end{gathered}

STEP 2: Applying the division rule of brackets:


x^m/ x^n=x^(m-n)

Therefore, the expression becomes:


\begin{gathered} \Rightarrow x^3\cdot y^(21-14) \\ \Rightarrow x^3\cdot y^7 \end{gathered}

ANSWER:

The simplified expression becomes:


\Rightarrow x^3y^7

User Lakerfield
by
5.3k points